(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
Dramatic discourse is a stylised form of communication in which conflict and harmony are central engines of plot development and characterisation. Because plays are built almost entirely out of talk, pragmatic markers—such as address terms, discourse markers, interjections, vocatives, repetitions, and formulaic expressions—become key resources for signalling tension, solidarity, aggression or reconciliation on stage. Unlike narrative prose, where description mediates interaction, dramatic dialogue foregrounds the immediacy of speech as social action. Every utterance performs relational work. In this sense, drama represents what Goffman (1967) conceptualised as “interaction ritual,” where face is continuously negotiated through verbal exchange. Recent work on dramatic pragmatics stresses that the language of plays, while scripted, is designed to imitate interactional reality and to exploit pragmatic mechanisms like speech acts, implicature and deixis in order to shape audience interpretation (Khursanov, 2025; Rasulova, 2024). The scripted nature of drama does not diminish its pragmatic authenticity; rather, it intensifies and stylises naturally occurring communicative processes to make relational dynamics theatrically visible.